Menembus Batas Fonetik : Perbandingan Pelafalan Vokal /ɛ/ dan /y/ Antara Mahasiswa Indonesia dan Penutur Asli Bahasa Prancis Melalui PRAAT - Masthuroh, Siti Ayu; Masruroh (Universitas Negeri Semarang, 2025)
The present study examines the differences in pronunciation of the vowels /ɛ/ and /y/ in French between Indonesian students as foreign speakers and native French speakers. The necessity to explore this topic arises from the fact that the Indonesian vowel system does not accommodate some vowels in French, which causes phonetic deviations in the process of foreign language acquisition. This current study focuses on describing the quality of pronunciation of the two vowels based on acoustic parameters using Praat software, and to recognize the forms of phonetic deviations that occur. The method used is a quantitative descriptive approach by analyzing acoustic data in the form of formant frequencies F1, F2 and F3 from the pronunciation recordings of ten participants. The results of the analysis show that the pronunciation of the vowel /y/ by Indonesian students experiences significant deviations, particularly in terms of lip rounding and articulatory position. This is reflected in the lower average F2 (1638.6 Hz) compared to native speakers (1975.6 Hz), and a much higher F3 (3183.2 Hz for non-native speakers versus 2416 Hz for natives). Meanwhile the vowel /ɛ/ shows more moderate differences, with an average F1 of 612 Hz for non-native speakers and 533 Hz for native speakers. These findings indicate the influence of phonological interference from the mother tongue on the production of French vowels. The findings of this research underscore the importance of technology-based phonetic teaching and intensive articulation training in learning French as a foreign language.